MILA, uma proposta de tecnologia na educação: uso de aplicativos com textos jornalísticos em sala de aula. - Erthal, Ana Luisa Montenegro (2023)
This research aims to collect data for the development of the MILA application, optimization suggestion the teaching-learning process through the critical reading of journalistic articles in the academic environment, whose target audience are teachers of the 6th year of Elementary School 2, of the private school Vila Aprendiz, in Recife. The proposal is to create a device with selected news, to be accessed in the classroom as a pedagogical support. For this, a semi-structured interview was carried out among the professors of the mentioned institution, together with an analysis of similars and the development of a screen prototype. This study proves to be relevant, since it aims to prove how the decoding of journalistic texts, extracted from printed vehicles, has multiple advantages in the teaching process, whether by reading itself, passing through the interpretation of texts and contextualization of school contents with the understanding of everyday situations. The main theoretical contributions are Freire (2019), Martin-Barbero (1995), Kaplún (1999), Cavalcanti (2003), Prensky (2011), Soares (2014) Jenkins (2015) and Tezani (2017). As a result, the interviewees accepted the proposal, received with enthusiasm, of potential in the citizenship formation of students and in social belonging. The work involves the areas of Communication, Education and Digital Information and Communication Technologies (TDICS), in accordance with the research line Technologies, Languages and Products of the Professional Graduate Program in Communication with a concentration area in Creative Industries at the University Catholic of Pernambuco.